2019
DOI: 10.1249/mss.0000000000002188
|View full text |Cite
|
Sign up to set email alerts
|

Oral l-Tyrosine Supplementation Improves Core Temperature Maintenance in Older Adults

Abstract: Introduction During cold exposure, an increase in sympathetic nerve activity evokes vasoconstriction (VC) of cutaneous vessels to minimize heat loss. In older adults, this reflex VC response is impaired thereby increasing their susceptibility to excess heat loss and hypothermia. Because l-tyrosine, the amino acid substrate necessary for catecholamine production, has been shown to augment reflex VC in age skin, we hypothesize that oral ingestion of l-tyrosine will attenuate the decline in core tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Consequently, the ability of cutaneous microvascular constriction is diminished in the elderly by increased oxidative stress [48][49] . Therefore, direct injection of BH4 [50] or tyrosine [51] or oral ingestion of a pharmacological source of BH4, sapropterin [52] or L-tyrosine [53][54] improved core temperature maintenance and augments the cutaneous reflex vasoconstriction response to cooling in older adults. Collectively, these studies demonstrate that reduced noradrenergic neurotransmitter biosynthesis may blunt reflex cutaneous vascular response to cold stress in older adults.…”
Section: Cutaneous Vasoconstrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the ability of cutaneous microvascular constriction is diminished in the elderly by increased oxidative stress [48][49] . Therefore, direct injection of BH4 [50] or tyrosine [51] or oral ingestion of a pharmacological source of BH4, sapropterin [52] or L-tyrosine [53][54] improved core temperature maintenance and augments the cutaneous reflex vasoconstriction response to cooling in older adults. Collectively, these studies demonstrate that reduced noradrenergic neurotransmitter biosynthesis may blunt reflex cutaneous vascular response to cold stress in older adults.…”
Section: Cutaneous Vasoconstrictionmentioning
confidence: 99%
“…This autoregulation driven by the sympathetic system causes vasodilation of coronary arteries to ensure constant coronary blood flow [41,[52][53][54][55] . The physically and functionally normal coronary arteries dilate in response to cold exposure [55] .…”
Section: Myocardial Work and Oxygen Supplymentioning
confidence: 99%
“…In the food industry, it is extensively used as a dietary supplement. For instance, it can be used as a nutritional supplement for patients with phenylketonuria, , a dietary supplement for patients with nemaline myopathy to improve strength and exercise tolerance, and an oral supplement to improve the vasoconstriction response of the elderly during whole-body cooling and to improve core temperature maintenance for the elderly who are facing acute cold exposure. , In addition, l -tyrosine decreases diastolic blood pressure and improves cognitive function under stress and attenuates mood disorders under low temperatures and hypoxic stress . In the medical field, l -tyrosine is used as a precursor for the synthesis of L-DOPA, which can be used as an essential anti-Parkinson’s medicine .…”
Section: Introductionmentioning
confidence: 99%
“…However, tyrosine is an essential substrate for tyrosine hydroxylase, which is involved in axonal catecholamine synthesis (particularly norepinephrine; Fernstrom & Fernstrom, 2007). Thus, sufficient tyrosine availability is required to maintain catecholamine levels and facilitate sympathetic vasoconstrictive effects on the subcutaneous vasculature (Lang et al, 2020). This has been reported to attenuate the rate of cold-induced decline in Tcore among those likely to have tyrosine deficiency (Lang et al, 2020), but there were no similar effects reported across studies conducted in the heat.…”
Section: Tyrosine Bcaas and Gabamentioning
confidence: 99%
“…Furthermore, among those with potential acute or chronic tyrosine deficiency, dietary supplementation may offer greater availability to maintain catecholamine levels, which are important for sympathetic vasoconstrictive effects on the subcutaneous vasculature (Lang et al, 2020) and may impact upon both dry and evaporative thermoregulatory defences. Given that both tyrosine and BCAAs may compete for the same blood-brain-barrier transporters, coupled with their wider roles in neurotransmitter biosynthesis pathways (Fernstrom, 1981;Pardridge, 1998;Suryawan et al, 1998), sufficient balance of both supplements may be important during heat exposure.…”
Section: Introductionmentioning
confidence: 99%